Ultra-thin high-strength lithium-magnesium-based alloy foil and its preparation method and application

In the field of lithium-ion batteries, the preparation method of lithium-magnesium-based alloy foil is adopted and solid solution strengthening and alloy strengthening technology is used to solve the problems of high preparation cost and short cycle life of existing lithium foils, and efficient prelithiated and long cycle life of lithium-ion batteries is achieved.

CN116426774BActive Publication Date: 2025-05-02NANJING TONGNING INSTITUTE OF NEW MATERIALS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310296887.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-24
Publication Date
2025-05-02
Estimated Expiration
2043-03-24

AI Technical Summary

Technical Problem

The existing ultra-thin lithium/lithium alloy foil is cost-effective in preparation, cumbersome use methods, and metal particles remain after prelithiation, which affects the cycle life of lithium-ion secondary batteries.

Method used

By adding magnesium element and other alloy elements to liquid lithium, lithium-magnesium-based alloy foil is formed, and ultra-thin high-strength lithium-magnesium-based alloy foil is prepared by solid solution strengthening and alloy strengthening methods, and through specific process conditions and element doping ratios, it can achieve efficient prelithization in the negative electrode materials of lithium-ion batteries.

Benefits of technology

It significantly improves the mechanical properties of the material, avoids the problem of transferring traditional lithium foils, and avoids the generation of metal debris through spontaneously formed hybrid ion electron conductor films, and extends the cycle life of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116426774B_ABST
    Figure CN116426774B_ABST
Patent Text Reader

Abstract

The present invention provides an ultra-thin high-strength lithium-magnesium-based alloy foil and a preparation method and application thereof. The preparation method comprises the following steps: step 1, in a first predetermined environment, heating lithium to a first predetermined temperature, after the lithium is completely melted into liquid lithium, adding magnesium to the liquid lithium at a predetermined atomic ratio, heating to a second predetermined temperature and stirring evenly to form a lithium-magnesium solid solution; step 2, in the first predetermined environment, adding M to the lithium-magnesium solid solution formed in step 1 at a predetermined atomic ratio, heating to a third predetermined temperature and stirring evenly, and waiting for the ingot to cool naturally; step 3, transferring the ingot after natural cooling in step 2 to a second predetermined environment, rolling to a predetermined thickness, and obtaining an ultra-thin high-strength lithium-magnesium-based alloy foil. The present invention finally obtains a pre-lithiation negative electrode material that can greatly improve the cycle life of a lithium battery, and the preparation process is simple, which is conducive to popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion secondary batteries and relates to an ultra-thin high-strength lithium-magnesium-based alloy foil and a preparation method and application thereof. Background Art

[0002] High-quality energy storage systems are the key to efficiently utilizing renewable energy, building smart grids, and facilitating energy transformation and upgrading. Due to the advantages of electrochemical energy storage systems such as fast response time and strong anti-interference ability, the installed capacity of electrochemical energy storage power stations in my country has also experienced explosive growth in recent years. Among various electrochemical energy storage technologies, lithium-ion secondary batteries have the largest cumulative installed capacity, accounting for more than 70%. With the rapid rise in the overall energy storage field, the market prospects for long-cycle lithium-ion secondary batteries will be even broader.

[0003] Pre-lithiation is considered to be an effective method to compensate for the formation of SEI on the negative electrode surface caused by the decomposition of the initial electrolyte in the battery, thereby greatly improving the battery cycle life. Among them, the method of using ultra-thin lithium metal / alloy foil to replenish lithium on the negative electrode has strong operability, high lithium replenishment efficiency, and good compatibility with existing electrode processes.

[0004] However, due to the poor processing performance of metallic lithium and its extremely active properties, the cost and risk of producing and using pre-lithiated ultra-thin lithium foil are very high. Traditional ultra-thin lithium foil often has an oil layer on the surface during processing, and its low strength requires it to be attached to a polymer substrate, which requires a lot of manpower and material resources to transfer the lithium foil. Although the use of alloy doping can improve the processing performance of lithium, such as CN110265654B, CN110265654B, etc., the irregular residue of alloy elements may deteriorate the cycle performance of the battery. Summary of the invention

[0005] The purpose of the present invention is to provide an ultra-thin high-strength lithium-magnesium-based alloy foil and a preparation method and application thereof, so as to solve the problems of high preparation cost, complicated use method and residual metal particles after pre-lithiation of the existing ultra-thin lithium / lithium alloy foil.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] The present invention provides a method for preparing an ultra-thin high-strength lithium-magnesium-based alloy foil, comprising the following steps:

[0008] Step 1: In a first predetermined environment, the lithium is heated to a first predetermined temperature, and after the lithium is completely melted into liquid lithium, a single magnesium substance is added to the liquid lithium at a predetermined atomic ratio, and the mixture is heated to a second predetermined temperature and stirred evenly to form a lithium-magnesium solid solution;

[0009] Step 2, in the first predetermined environment, adding M to the lithium-magnesium solid solution formed in step 1 at a predetermined atomic ratio, heating to a third predetermined temperature and stirring evenly, and waiting for the ingot to cool naturally;

[0010] Step three, transferring the naturally cooled ingot in step two to a second predetermined environment, rolling it to a predetermined thickness, and obtaining an ultra-thin high-strength lithium-magnesium-based alloy foil.

[0011] Preferably, in step one, the first predetermined environment is an argon atmosphere or a vacuum atmosphere, the oxygen concentration is lower than 10 ppm, and the water vapor concentration is lower than 0.1 ppm; more preferably, the oxygen concentration is lower than 1 ppm, and the water vapor concentration is lower than 0.01 ppm; the first predetermined temperature range is 180-220°C, more preferably 190-210°C.

[0012] Preferably, in step 1, the predetermined atomic ratio of magnesium to lithium is 2% to 5%, more preferably 2% to 4%. The magnesium element may be in the form of magnesium powder / magnesium foil / magnesium block / other morphologies.

[0013] Preferably, in step 1, the second predetermined temperature range is 200-300°C, more preferably 220-240°C.

[0014] Preferably, in step 2, M can be at least one of B, Al, Ag, Sn, Zn, Sb, and In, more preferably Al; the predetermined atomic ratio of M to magnesium is 50% to 200%, more preferably 90% to 110%.

[0015] Preferably, in step 2, the third predetermined temperature range is 220-350°C, more preferably 230-280°C.

[0016] Preferably, in step three, the relative humidity of the second predetermined environment is lower than 15%.

[0017] Preferably, in step three, the predetermined thickness range is 5 μm or less.

[0018] The present invention also provides an ultra-thin high-strength lithium-magnesium-based alloy foil, which is prepared by the above preparation method.

[0019] The present invention further provides the use of the ultra-thin high-strength lithium-magnesium-based alloy foil in the pre-lithiation of negative electrode materials for lithium-ion batteries.

[0020] The beneficial effects of the present invention are:

[0021] (I) The present invention greatly improves the mechanical properties of the material through solid solution strengthening and alloy strengthening, which enables it to maintain a self-supporting structure when rolled to less than 5μm, thereby avoiding the transfer problem when using traditional ultra-thin lithium foil. At the same time, the alloy elements can help the surface of the metal lithium form a denser and stronger oxide film, avoiding the occurrence of roller sticking and internal corrosion of the grain boundary.

[0022] (ii) The present invention creatively controls the atomic ratio of the doping elements Mg and M to be above 2%, so that after pre-lithiation, a mixed ion-electron conductor film is spontaneously formed, avoiding the conversion into metal debris as in the pre-lithiation of metallic lithium; at the same time, the atomic ratio of the two elements is controlled to be less than 5%, avoiding the phenomenon that the remaining film is too thick and affects the subsequent cycle of the battery.

[0023] (III) The present invention finally obtains a pre-lithiation negative electrode material that can greatly improve the cycle life of lithium batteries. The preparation process is simple and is conducive to popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is the XRD diffraction peak of the alloy foil in Example 1 of the present invention.

[0025] Figure 2 This is the X-ray photoelectron spectrum (O1s) of the alloy foil in Example 1 of the present invention.

[0026] Figure 3 This is a tensile test of the alloy foil in Example 1 of the present invention.

[0027] Figure 4 The photographs show the cycle performance of the full battery in Example 1 of the present invention and the composite electrode after standing in the electrolyte.

[0028] Figure 5 The photographs show the cycle performance of the full battery in Example 2 of the present invention and the composite electrode after standing in the electrolyte.

[0029] Figure 6 This is the cycle performance of the full battery in Example 3 of the present invention.

[0030] Figure 7 This is the cycle performance of the full battery in Example 4 of the present invention.

[0031] Figure 8 This is the cycle performance of the full battery in Comparative Example 1 of the present invention.

[0032] Fig. 9 The photographs are of the cycle performance of the full battery in Comparative Example 2 of the present invention and the composite electrode after standing in the electrolyte.

[0033] Fig.10 The photographs are of the cycle performance of the full battery in Comparative Example 3 of the present invention and the composite electrode after standing in the electrolyte.

[0034] Fig.11 This is the cycle performance of the full battery in Comparative Example 4 of the present invention.

[0035] Fig.12 This is the cycle performance of the full battery in Comparative Example 5 of the present invention. DETAILED DESCRIPTION

[0036] The present invention is described in more detail below through examples and drawings. The various product structural parameters, various reaction participants and process conditions used in the following examples are all typical examples, but after a large number of experiments and verifications by the inventor of this case, other different structural parameters, other types of reaction participants and other process conditions listed above are also applicable and can also achieve the technical effects claimed by the present invention.

[0037] Example 1

[0038] In a high-purity argon protective atmosphere, metallic lithium is heated to 190°C. After the lithium is completely melted, magnesium foil is added to the metallic lithium at a content of 2 atomic percent, the temperature is raised to 220°C, and stirred to allow the magnesium to be completely dissolved in the metallic lithium; aluminum foil is then added to the above solid solution at a content of 2 atomic percent, and the temperature is raised to 230°C; after the ingot is cooled, it is transferred to a drying room with a relative humidity of 10% and rolled to 5μm using a roller press.

[0039] The obtained alloy foil was pasted on a surface with a capacity of 4.5 mAh / cm 2 The surface of the graphite negative electrode is obtained to obtain a composite negative electrode; the composite negative electrode is matched with a surface capacity of 3.3 mAh / cm 2 The lithium iron phosphate positive electrode was assembled into a CR2025 button cell in an argon-protected glove box. After the above battery was formed at room temperature with a low current of 0.05C for 5 cycles and 0.3C for 10 cycles, a long cycle test with a rate of 1C was performed, and the full battery voltage range was [2.5V, 3.8V].

[0040] from Figure 1 It can be seen that the alloy foil is mainly composed of Li(Mg) phase and Li-Al intermetallic compound.

[0041] from Figure 2 It can be seen that there are abundant magnesium- and aluminum-containing oxide films in the area below 50 nm of the alloy foil. The presence of these oxides is the key to the alloy foil not sticking to the roller during rolling.

[0042] from Figure 3 It can be seen that the tensile strength of the alloy foil reaches an astonishing 14MPa, which is an order of magnitude higher than that of pure lithium. This is the key to the continuous stripping of the alloy foil during rolling.

[0043] from Figure 4 It can be seen that after lithiation occurs, the alloy foil in this embodiment spontaneously forms a film on the surface of the graphite negative electrode. The battery has no capacity decay in the first 500 cycles. After 500 cycles, the capacity decay rate is about 0.01% / cycle, which proves that the lithium alloy foil in this embodiment has no negative impact on the battery cycle.

[0044] Example 2

[0045] In a high-purity argon protective atmosphere, metallic lithium is heated to 210°C. After the lithium is completely melted, magnesium foil is added to the metallic lithium at a content of 4 atomic percent, the temperature is raised to 240°C, and stirred to allow the magnesium to be completely dissolved in the metallic lithium; aluminum foil is then added to the above solid solution at a content of 4 atomic percent, and the temperature is raised to 280°C; after the ingot is cooled, it is transferred to a drying room with a relative humidity of 10% and rolled to 5μm using a roller press.

[0046] The obtained alloy foil was pasted on a surface with a capacity of 4.5 mAh / cm 2 The surface of the graphite negative electrode is obtained to obtain a composite negative electrode; the composite negative electrode is matched with a surface capacity of 3.3 mAh / cm 2 The lithium iron phosphate positive electrode was assembled into a CR2025 button cell in an argon-protected glove box. After the above battery was formed at room temperature with a low current of 0.05C for 5 cycles and 0.3C for 10 cycles, a long cycle test with a rate of 1C was performed, and the full battery voltage range was [2.5V, 3.8V].

[0047] from Figure 5 It can be seen that after lithiation occurs, the alloy foil in this embodiment spontaneously forms a film on the surface of the graphite negative electrode. The battery has no capacity decay in the first 500 cycles. After 500 cycles, the capacity decay rate is about 0.01% / cycle, which proves that the lithium alloy foil in this embodiment has no negative impact on the battery cycle.

[0048] Example 3

[0049] In a high-purity argon protective atmosphere, metallic lithium is heated to 200°C. After the lithium is completely melted, magnesium foil is added to the metallic lithium at a content of 3 atomic percent, the temperature is raised to 230°C, and stirred to allow the magnesium to be completely dissolved in the metallic lithium; then silver foil is added to the above solid solution at a content of 3.3 atomic percent, and the temperature is raised to 250°C; after the ingot is cooled, it is transferred to a drying room with a relative humidity of 15% and rolled to 4μm using a roller press.

[0050] The obtained alloy foil was pasted on a surface with a capacity of 4.5 mAh / cm 2 The surface of the graphite negative electrode is obtained to obtain a composite negative electrode; the composite negative electrode is matched with a surface capacity of 3.3 mAh / cm 2The lithium iron phosphate positive electrode was assembled into a CR2025 button cell in an argon-protected glove box. After the above battery was formed at room temperature with a low current of 0.05C for 5 cycles and 0.3C for 10 cycles, a long cycle test with a rate of 1C was performed, and the full battery voltage range was [2.5V, 3.8V].

[0051] from Figure 6 It can be seen that the battery has no capacity decay in the first 250 cycles, and the capacity decay rate is about 0.02% / cycle after 500 cycles, which proves that the lithium alloy foil in this embodiment has no negative impact on the battery cycle.

[0052] Example 4

[0053] In a high-purity argon protective atmosphere, metallic lithium is heated to 200°C. After the lithium is completely melted, magnesium foil is added to the metallic lithium at a content of 2 atomic percent, the temperature is raised to 230°C, and stirred to allow the magnesium to be completely dissolved in the metallic lithium; tin foil is then added to the above solid solution at a content of 1.8 atomic percent, and the temperature is raised to 250°C; after the ingot is cooled, it is transferred to a drying room with a relative humidity of 15% and rolled to 3μm using a roller press.

[0054] The obtained alloy foil was pasted on a surface with a capacity of 4.5 mAh / cm 2 The surface of the graphite negative electrode is obtained to obtain a composite negative electrode; the composite negative electrode is matched with a surface capacity of 3.3 mAh / cm 2 The lithium iron phosphate positive electrode was assembled into a CR2025 button cell in an argon-protected glove box. After the above battery was formed at room temperature with a low current of 0.05C for 5 cycles and 0.3C for 10 cycles, a long cycle test with a rate of 1C was performed, and the full battery voltage range was [2.5V, 3.8V].

[0055] from Figure 7 It can be seen that the battery has no capacity decay in the first 150 cycles, and the capacity decay rate is about 0.015% / cycle after 500 cycles, which proves that the lithium alloy foil in this embodiment has no negative impact on the battery cycle.

[0056] Comparative Example 1

[0057] The surface capacity is 3.5 mAh / cm 2 The graphite anode matches 3.3mAh / cm 2 The lithium iron phosphate positive electrode was used and CR2025 button cells were assembled in an argon-protected glove box. After the above batteries were formed at room temperature with a low current of 0.05C for 5 cycles and 0.3C for 10 cycles, a long cycle test with a rate of 1C was performed, and the full battery voltage range was [2.5V, 3.8V].

[0058] like Figure 8As shown, the battery loses most of its capacity during the formation stage, and the capacity loss rate after formation is about 0.02% / cycle.

[0059] Comparative Example 2

[0060] The surface capacity of the commercial 5μm lithium foil is 4.5mAh / cm 2 The surface of the graphite negative electrode is obtained to obtain a composite negative electrode; the composite negative electrode is matched with a surface capacity of 3.3 mAh / cm 2 The lithium iron phosphate positive electrode was assembled into a CR2025 button cell in an argon-protected glove box. After the above battery was formed at room temperature with a low current of 0.05C for 5 cycles and 0.3C for 10 cycles, a long cycle test with a rate of 1C was performed, and the full battery voltage range was [2.5V, 3.8V].

[0061] from Fig. 9 It can be seen that after lithiation, the metallic lithium is broken on the graphite surface, and much of it is not absorbed by the graphite. The battery has a slightly higher capacity than Comparative Example 1 in the initial 100 cycles, but due to the presence of broken lithium, its capacity decay in subsequent cycles is much faster than that of Comparative Example 1, indicating that it is not suitable for pre-lithiation of graphite.

[0062] Comparative Example 3

[0063] In a high-purity argon protective atmosphere, metallic lithium is heated to 210°C. After the lithium is completely melted, magnesium foil is added to the metallic lithium at a content of 1 atomic ratio, the temperature is raised to 240°C, and stirred to make the magnesium completely dissolved in the metallic lithium; aluminum foil is then added to the above solid solution at a content of 1 atomic ratio, and the temperature is raised to 280°C; after the ingot is cooled, it is transferred to a drying room with a relative humidity of 10% and rolled to 5μm using a roller press.

[0064] The obtained alloy foil was pasted on a surface with a capacity of 4.5 mAh / cm 2 The surface of the graphite negative electrode is obtained to obtain a composite negative electrode; the composite negative electrode is matched with a surface capacity of 3.3 mAh / cm 2 The lithium iron phosphate positive electrode was assembled into a CR2025 button cell in an argon-protected glove box. After the above battery was formed at room temperature with a low current of 0.05C for 5 cycles and 0.3C for 10 cycles, a long cycle test with a rate of 1C was performed, and the full battery voltage range was [2.5V, 3.8V].

[0065] from Fig.10 It can be seen that after lithiation, the alloy foil was broken on the graphite surface, and much of it was not absorbed by the graphite. The battery capacity in the initial 500 cycles was slightly higher than that in Comparative Example 1, but there were still broken alloy particles. Although the capacity decay in the subsequent cycles was better than that in Comparative Example 2, it was still much faster than that in Comparative Example 1, indicating that it is not suitable for pre-lithiation of graphite.

[0066] Comparative Example 4

[0067] In a high-purity argon protective atmosphere, metallic lithium is heated to 210°C. After the lithium is completely melted, magnesium foil is added to the metallic lithium at a content of 6 atomic percent, the temperature is raised to 240°C, and stirred to allow the magnesium to be completely dissolved in the metallic lithium; aluminum foil is then added to the above solid solution at a content of 6 atomic percent, and the temperature is raised to 280°C; after the ingot is cooled, it is transferred to a drying room with a relative humidity of 10% and rolled to 5μm using a roller press.

[0068] The obtained alloy foil was pasted on a surface with a capacity of 4.5 mAh / cm 2 The surface of the graphite negative electrode is obtained to obtain a composite negative electrode; the composite negative electrode is matched with a surface capacity of 3.3 mAh / cm 2 The lithium iron phosphate positive electrode was assembled into a CR2025 button cell in an argon-protected glove box. After the above battery was formed at room temperature with a low current of 0.05C for 5 cycles and 0.3C for 10 cycles, a long cycle test with a rate of 1C was performed, and the full battery voltage range was [2.5V, 3.8V].

[0069] from Fig.11 It can be seen that the battery has a slightly higher cycle capacity than comparative example 1 in the initial 500 cycles, but its capacity decay in subsequent cycles is better than that in comparative example 2, but still much faster than that in comparative example 1, indicating that it is not suitable for pre-lithiation of graphite.

[0070] Comparative Example 5

[0071] In a high-purity argon protective atmosphere, metallic lithium is heated to 210°C. After the lithium is completely melted, magnesium foil is doped into the metallic lithium at a content of 2 atomic percent, the temperature is raised to 240°C, and stirred to allow the magnesium to be completely dissolved in the metallic lithium. After the ingot is cooled, it is transferred to a drying room with a relative humidity of 10% and rolled to 5μm using a roller press.

[0072] The obtained alloy foil was pasted on a surface with a capacity of 4.5 mAh / cm 2 The surface of the graphite negative electrode is obtained to obtain a composite negative electrode; the composite negative electrode is matched with a surface capacity of 3.3 mAh / cm 2 The lithium iron phosphate positive electrode was assembled into a CR2025 button cell in an argon-protected glove box. After the above battery was formed at room temperature with a low current of 0.05C for 5 cycles and 0.3C for 10 cycles, a long cycle test with a rate of 1C was performed, and the full battery voltage range was [2.5V, 3.8V].

[0073] from Fig.12It can be seen that after lithiation occurs, the battery capacity decays rapidly after the battery rate increases, and the coulombic efficiency is far below 100%. This is caused by the increase in polarization caused by the transformation of the Li(Mg) solid solution to non-lithiated Mg(Li) after a certain amount of delithiation, which indicates the necessity of forming a partially lithium-conducting intermetallic compound in the matrix of the pre-lithiated alloy foil.

[0074] The inventors found that the reason why lithium metal sticks to the roller is that "reactive wetting" occurs between the lithium and the roller interface, that is, the lithium metal breaks through the "constraints" of the originally fragile oxide film during the rolling process, and locally "cold welds" with the stainless steel roller under the action of pressure. At the same time, lithium itself has low tensile strength, and the rolling process is prone to belt breakage, resulting in discontinuous production. The inventors found that solid solution strengthening and alloy strengthening can greatly improve the mechanical properties of the material, which allows it to maintain a self-supporting structure when rolled to less than 5μm, thereby avoiding the transfer problem when using traditional ultra-thin lithium foil. At the same time, alloy elements can help form a denser and stronger oxide film on the surface of lithium metal, avoiding the phenomenon of sticking to the roller and the occurrence of internal corrosion at the grain boundaries.

[0075] In addition, the inventors also revealed the design ideas of lithium alloy foil for pre-lithiation of negative electrode materials of lithium-ion batteries. When metallic lithium is used for pre-lithiation, after the part of lithium in contact with graphite is absorbed by graphite, the subsequent lithiation process will no longer proceed due to the disappearance of the electron path; when binary lithium solid solution represented by lithium magnesium is used for pre-lithiation, due to the slow diffusion of lithium in lithium magnesium, before the lithium far from the graphite side has time to be absorbed by graphite, the alloy close to the graphite side has been converted into the Mg (Li) phase that does not conduct lithium, and the lithium ion path disappears; and when binary alloys that form intermetallic compounds represented by lithium aluminum are used for pre-lithiation, since the potential of the intermetallic compound is generally higher than the working potential of graphite, the stored lithium is difficult to be absorbed by graphite. Therefore, only by using lithium magnesium solid solution as the substrate, further doping it with elements that alloy with lithium and making it dispersed in the substrate to conduct lithium ions, can the efficient utilization of lithium during pre-lithiation be achieved. The inventors found that only when the atomic ratio of Mg and M in the doping elements is controlled at above 2%, can a mixed ion-electronic conductor film be spontaneously formed after pre-lithiation, avoiding turning into metal debris like pre-lithiation of metallic lithium; at the same time, the atomic ratio of the two elements needs to be less than 5%, otherwise the remaining film will be too thick and affect the subsequent cycle of the battery.

[0076] Obviously, the above embodiments of the present invention are merely examples to more clearly illustrate the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing an ultra-thin high-strength lithium-magnesium-based alloy foil, comprising the following steps: Step 1: In a first predetermined environment, lithium is heated to a first predetermined temperature, and after the lithium is completely melted into liquid lithium, magnesium is added to the liquid lithium at a predetermined atomic ratio of magnesium to lithium of 2% to 5%, and the mixture is heated to a second predetermined temperature and stirred evenly to form a lithium-magnesium solid solution, wherein the first predetermined environment is an argon atmosphere or a vacuum atmosphere, the oxygen concentration is less than 10 ppm, and the water vapor concentration is less than 0.1 ppm; the first predetermined temperature range is 180 to 220° C., and the second predetermined temperature range is 200 to 300° C.; Step 2, in a first predetermined environment, adding M to the lithium-magnesium solid solution formed in step 1 at a predetermined atomic ratio of M to magnesium of 50% to 200%, wherein M is at least one of B, Al, Ag, Sn, Zn, Sb, and In, heating to a third predetermined temperature and stirring evenly, and waiting for the ingot to cool naturally, wherein the third predetermined temperature ranges from 220 to 350° C.; Step three, transferring the ingot after natural cooling in step two to a second predetermined environment, rolling it to a predetermined thickness to obtain an ultra-thin high-strength lithium-magnesium-based alloy foil, wherein the predetermined thickness range is 5 μm and below, and the relative humidity of the second predetermined environment is lower than 15%.

2. An ultra-thin high-strength lithium-magnesium-based alloy foil, prepared by the method for preparing an ultra-thin high-strength lithium-magnesium-based alloy foil according to claim 1.

3. Application of the ultra-thin high-strength lithium-magnesium-based alloy foil as described in claim 2 in pre-lithiation of negative electrode materials for lithium-ion batteries.

Citation Information

Patent Citations

  • An ultrathin lithium-silver alloy strip for lithium-ion battery anode and its preparation method

    CN110265654B

  • Ultrathin lithium-silver alloy strip for lithium ion battery anode and preparation method thereof

    CN110265654A

  • Electrode materials in the form of lithium-based alloy and methods for manufacturing same

    CN110998920A